The Impact of the Sustainable Strategy on Strategic Performance: Field Study in the Iraqi Tourism Sector - Alsaad, Muslim Alawi; Lazim, Yusra Yaseen (South Asian Journal of Social Sciences and Humanities, 2023)
The tourism industry, with its two sides (recreational and religious), is one of the important  investment fields in Iraq, it is represented Iraq as the second economic source after the oil  sector. So a need for serious efforts to develop the tourism sector and maintain its sustainability.  This paper will be one of the important contributions in this field; the paper aims to explore the  extent of the impact of the sustainable strategy on the level of overall performance in the Iraqi  tourism sector. The field of research was some Iraqi tourist institutions at Iraqi tourism, Which  covers the field of study on the one side, and can be studied on the other side, for the developing  study methodology and organizing its main parts, the research paper adopted a major hypothesis  that (there is a statistically significant effect of the sustainable strategy on the level of the  overall performance of the Iraqi tourism sector), and for data collection, a checklist was used. The checklist In its questions covers the content required from the study of some tourist  institutions in the Iraqi tourism sector, and the list was distributed to a sample of people  working in the Iraqi tourism sector, size of the sample (43 people), with experience and  academic specialization. The study reached a set of results, the most important of which are: the  ability of the sustainable strategy to ensure continuously improve the overall tourism sector  performance.
Keywords: Strategic perspective; Sustainable strategy; Overall performance; tourism sector